Pengaruh Plugging Terhadap Kinerja High Pressure Heater Tipe Shell and U-Tube Heat Exchanger (Studi Kasus: Unit 1- 4 di PT ABC) - Muhammad, Ghaffar; Arirohman, Ilham Dwi; Naimah, Khoirun (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
High Pressure Heater (HPH) is an auxiliary component used to be required in regenerative steam power plants. The component is a heat exchanger utilized to enhance the power plant’s efficiency by enabling high pressure heating process for feedwater before entering the economizer in boiler using bled steam from turbine. The heat transfer effectiveness of HPH needs to be evaluated in relation to its operational conditions which are equipped with plugs to overcome leaks. This study aims to evaluate the impact of number of plugs on the high-pressure heater 5 in unit 1-4 PT ABC regarding heat transfer and its effectiveness. The Number of Transfer Unit (NTU) method along with Log Mean Temperature Difference (LMTD) method were employed in analysis of this research. The existing number of plugs are 4, 574, 100, and 111 in unit 1, 2, 3, and 4 respectively. The result shows that the heat transfer value for high pressure heaters in unit 1-4 PT ABC are 16.18 MW, 10.32 MW, 15.20 MW and 15.08 MW respectively, while the effectiveness value are 0.89, 0.74, 0.88, and 0.88. The study concludes that the effect of number of plugs in high-pressure heater regarding to heat transfer and effectiveness tends to be inversely linear.